Energy dependence of J/ψ production in Au + Au collisions at √sNN=39,62.4 and 200GeV - STAR Collaboration (Physics Letters B, 2017)
The inclusive J/ψ transverse momentum spectra and nuclear modification factors are reported at mid-rapidity (|y|<1.0) in Au + Au collisions at sNN = 39, 62.4 and 200 GeV taken by the STAR experiment. A suppression of J/ψ production, with respect to the production in p+p scaled by the number of binary nucleon–nucleon collisions, is observed in central Au + Au collisions at these three energies. No significant energy dependence of nuclear modification factors is found within uncertainties. The measured nuclear modification factors can be described by model calculations that take into account both suppression of direct J/ψ production due to the color screening effect and J/ψ regeneration from recombination of uncorrelated charm–anticharm quark pairs. © 2017 The Author
Keywords: dept.phy; peer-reviewed